Design of New Dynamic Cryptosystem with High Software Protection - Ghazi, Abdullah Ayad; Ali, Faez Hassan (Iraqi Journal of Science, 2018)
In this paper a design of new robust and dynamic cryptosystem using stream key generator with good random statistical properties is introduced. The results of the statistical tests, initialization and the components of the proposed generator of the suggested cryptosystem are detailed in [1]. The proposed cryptosystem called Robust and Efficient Dynamic Stream Cipher Cryptosystem (RDSCC). The dynamic here means the generator of RDSCC has unfixed construction; the design will be changed as the seed (initial) key changed. The generator will construct itself by barrows number of Linear Feedback Shift Registers (LFSR’s), randomly, stored in protected bank file. The RDSCC is constructed to be flexible to encrypt (decrypt) different types of data; like message text and image data efficiently. Also we suggest using software protection for RDSCC which is represented by partitioned the cryptosystem file into two parts, each one saved in different memories to keep it in save from any attack. Lastly, the proposed generator and the cryptosystem are implemented practically and the main interfaces of the two programs are shown in this paper. These interfaces are programmed with GUI MATLAB2017.